Manual on uniform traffic control devices : for streets and highways. (U.S. Dept. of Transportation, Federal Highway Administration, 2009)
This 2009 edition defines the standards used by road managers nationwide to install and maintain traffic control devices on all public streets, highways, bikeways, and private roads open to public traffic. This manual is published by the Federal Highway Administration (FHWA) under 23 Code of Federal Regulations (CFR), Part 655, Subpart F.